Nasopharyngeal Non Hodgkin Lymphoma - Wardhani, Shinta Oktya; Kartikasari, Nanik Triana (Fakultas Kedokteran Universitas Brawijaya, 2017)
Non Hodgkin lymphomas (NHL) are tumors originating from lymphoid tissue, mainly from lymph nodes. These tumors may result from chromosomal translocation, infections, environmental factors, immunodeficiency states, and chronic inflammation. In general, the incidence of NHL is slightly higher in men than in women. The incidence of NHL nasopharynx is rare. A high degree of suspicion is required to avoid unnecessary radiologic and surgical procedures since NHL can be mistakenly diagnosed as carcinoma. We reported a 16 year old male patient with gradual epistaxis, hearing impairment, decreased body weight, and multiple nodules in right forehead, right axilla, right colli posterior, and left waist. The patient also suffered from inferior paraplegic extremities. The Head CT scan result showed carcinoma nasopharynx. After biopsy of nodules was done, it revealed differential diagnoses such as blastoma, Non Hodgkin lymphoma, and small cell carcinoma. Immunohistochemistry result showed Leucocyte Common Antigen (LCA) positive, and MRI thorax showed suspect of schwannoma. Based on the data, chemotherapy with regiment CHOP (cyclophosphamide, hydroxydaunorubicin, oncovin/vincristine, and prednisone) was given. The prognosis of NHL Nasopharynx was better than nasopharyngeal squamous cell carcinoma. The prognostic of NHL depends on the age, performance status, staging, extranodal involvement, serum Lactate Dehydrogenase (LDH) and response of therapy. The prognosis in our patient was poor.Keywords: Mass, Non Hodgkin Lymphoma, nasopharyngeal carcinoma, prognostic